Soybean Cost-Return Budget in South Central Kansas - Gerald W. Warmann (My University, 1999)
This publication provides estimated cost and returns for forward farm planning for soybeans in south central Kansas.
MF2156_1999_10
Keywords: MF2156; Crops; Economics; MF